Quelle traduction ! A study of the translation of French quel and English what exclamatives in political discourse - Troughton, Faye (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
This paper reports on a study of the translation of English what and French quel exclamatives spoken in European Parliament proceedings into French and English respectively. It explores how these meaning-laden constructions are translated in practice as well as the translation of associated degree modifying and performative elements. This paper also argues that corpus-based translation studies can contribute to the debate surrounding the definition of the embedded (non-matrix) exclamatives and touches upon the comparative use of these exclamatives in the two languages.